The Effect of the Flipped Classroom Model Assisted Google Classroom on Learning Result and Student's Responses in Subject Straight Motion Dynamics in Senior High School - Melisa Putri Febriyanti; Singgih Bektiarso; Maryani Maryani (International Journal Labs, 2023)
The low physics learning outcomes of students are influenced by several factors, namely the selection of learning models and media that are less supportive so students are less responsive to learning. The purpose of this study is to examine the effect of the Flipped Classroom model assisted by Google Classroom on student learning outcomes and describe student responses to the Flipped Classroom model assisted by Google Classroom on straight-motion dynamics material. This research is an experimental research using a posttest-only control group design. The sample selection was done by cluster random sampling method. Data collection methods consist of observation, interviews, documentation, written tests, and questionnaires. The data analysis technique of learning outcomes used an independent sample t-test, while student responses used score criteria. The results showed that the Sig. (2-tailed) in the t-test using SPSS is 0.000 (? 0.05). Then, for the results of experimental class student responses, the results of the response aspect were 82.58% and the reaction aspect was 83.44%, both of which were in the interval 80 ? P ? 100 with a very good category. The conclusion obtained is that there is a significant effect of the application of the Flipped Classroom model assisted by Google Classroom on the learning outcomes of students of SMAN 3 Jember on the material of the dynamics of straight motion. Then, the results of student responses to the application of the Flipped Classroom model assisted by Google Classroom on the material of the dynamics of straight motion obtained positive responses and reactions and included in the very good criteria.